Mast cell density and distribution in human abdominal aortic aneurysm - Sakamoto, Sumiharu; Tsuruda, Toshihiro; Hatakeyama, Kinta; Sekita, Yoko; Imamura, Takuroh; Asada, Yujiro; Kitamura, Kazuo (IntechOpen, 2011)
None